High Flow Nasal Cannula Oxygen Therapy in Long Hauler Covid-19 Patients - Sarinti Sarinti; Fefi Eka Wahyuningsih (University of Muhammadiyah Semarang, 2021)
Long Hauler Covid-19 is a condition that describes a person who has recovered from Covid-19 and is declared with a negative PCR smear 2 times but still feels signs and symptoms for a longer period of time, even severe and critical symptoms. Most cases complicate Acute Respiratory Disorder Syndrome (ARDS), which can lead to death. Fulfilment of non-invasive high concentration oxygenation requirements as an intervention modality in this case. The purpose of this case study was to determine the effect of giving oxygen therapy through the High Flow Nasal Cannula (HFNC) on the respiratory function of Covid-19 long haulier patients. The method of nursing care was a case study on 2 respondents with a descriptive approach method. There were 2 cases of Long haulier Covid-19 patients with comorbid smokers, Diabetes Mellitus, experiencing moderate ARDS complications, desaturation, and tachypnea. Patients received oxygen therapy intervention through HFNC while being treated in the critical care room, and after being given HFNC oxygen therapy for 5 days there was a decrease in respiratory frequency, a change in breathing pattern from shortness of breath to shortness of breath, an increase in oxygen saturation, an increase in the ROX Index, an increase in PO2 and blood pH in normal limit. Nursing care that focuses on respiratory management in covid-19 long haulier patients improves patient outcomes in particular, namely decreased respiratory rate, changes in the respiratory pattern of shortness of breath, increased oxygen saturation, increased ROX index, increased PO2 and blood pH within normal limits.